2020
DOI: 10.7150/ijbs.38950
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of Kv1.3 regulates macrophage migration in acute liver injury by targeting δ-catenin through RhoA signaling

Abstract: Background: Activation of macrophages and infiltration are key events in acute liver injury (ALI). Kv1.3 plays an important role in regulating immunologic functions of macrophages and is extensively recognized as a potential ion channel for immunological diseases. Objective: We hypothesized that blockage of Kv1.3 may influence ALI by inhibiting macrophages infiltration in damaged liver tissues. Methods: Margatoxin was administered into the peritoneal cavity of ALI mice. The impact of this treatment on ALI and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…In addition, the calculated extravasation index suggests that K V 1.3 might also be involved in neutrophil transmigration across the inflamed endothelium. This hypothesis is supported by reports revealing that interference with K V 1.3 reduces cell migration in macrophages, 44 , 45 T cells, 40 or microglia cells, 46 too.…”
Section: Discussionsupporting
confidence: 67%
“…In addition, the calculated extravasation index suggests that K V 1.3 might also be involved in neutrophil transmigration across the inflamed endothelium. This hypothesis is supported by reports revealing that interference with K V 1.3 reduces cell migration in macrophages, 44 , 45 T cells, 40 or microglia cells, 46 too.…”
Section: Discussionsupporting
confidence: 67%
“…Notably, Tang et al [ 32 ] have recently found that CTNND1(delta-catenin) was highly expressed in HCC tissues and dramatically enhanced Wnt/β-catenin signaling, indicating CTNND1 might act as a regulator of the canonical Wnt/β-catenin signaling pathway [ 33 ]. Although CTNND1 has been shown to be associated with macrophage migration and influence macrophage in the inflammatory response [ 34 , 35 ], whether CTNND1 can promote the M2 polarization through activating canonical Wnt/β-catenin signaling pathway in HCC-TAMs remains to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of K V 1.3 channels suppresses antigen-driven proliferation and cytokine production in T cells and macrophages. Therefore, selective K V 1.3 channel blockers ameliorate different pathologies that involve inflammation including multiple sclerosis, autoimmune diabetes and acute liver injury (Beeton et al, 2005;Beeton, Wulff, et al, 2001;Chi et al, 2012;Rus et al, 2005;Wu et al, 2020 (Qian et al, 2014) and 4 weeks (Qi et al, 2019;Ye et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of K V 1.3 channels suppresses antigen‐driven proliferation and cytokine production in T cells and macrophages. Therefore, selective K V 1.3 channel blockers ameliorate different pathologies that involve inflammation including multiple sclerosis, autoimmune diabetes and acute liver injury (Beeton et al, 2005; Beeton, Barbaria, et al, 2001; Beeton, Wulff, et al, 2001; Chi et al, 2012; Rus et al, 2005; Wu et al, 2020). Our study demonstrates that K V 1.3 channels are important determinants of macrophage phenotype in AngII‐induced hypertension, which in turn participates in endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%